2014
DOI: 10.1016/j.neuropharm.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Repeated intermittent alcohol exposure during the third trimester-equivalent increases expression of the GABAA receptor δ subunit in cerebellar granule neurons and delays motor development in rats

Abstract: Exposure to ethanol (EtOH) during fetal development can lead to long-lasting alterations, including deficits in fine motor skills and motor learning. Studies suggest that these are, in part, a consequence of cerebellar damage. Cerebellar granule neurons (CGNs) are the gateway of information into the cerebellar cortex. Functionally, CGNs are heavily regulated by phasic and tonic GABAergic inhibition from Golgi cell interneurons; however, the effect of EtOH exposure on the development of GABAergic transmission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 100 publications
7
31
0
1
Order By: Relevance
“…In addition, we previously found that exposure to lower levels of ethanol (i.e., 0.1 g/dl) during the 3 rd trimester equivalent have relatively subtle effects on synaptic transmission in the amygdala (Diaz et al, 2014a) and wished to test a higher dose of ethanol that was comparable to that used in other studies of the effect of exposure during this period on anxiety-like behavior in mature rats (Roskam and Koch, 2009). In general agreement with previous studies (Puglia and Valenzuela, 2010, Everett et al, 2012, Diaz et al, 2014b), the paradigm minimally affected pup weight gain or nursing ability. Maternal care was also minimally altered, consistent with the finding that serum ethanol concentrations in the dam were less than 10% of the levels found in the pup, which is likely due to increased ability to metabolize ethanol in the dams.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we previously found that exposure to lower levels of ethanol (i.e., 0.1 g/dl) during the 3 rd trimester equivalent have relatively subtle effects on synaptic transmission in the amygdala (Diaz et al, 2014a) and wished to test a higher dose of ethanol that was comparable to that used in other studies of the effect of exposure during this period on anxiety-like behavior in mature rats (Roskam and Koch, 2009). In general agreement with previous studies (Puglia and Valenzuela, 2010, Everett et al, 2012, Diaz et al, 2014b), the paradigm minimally affected pup weight gain or nursing ability. Maternal care was also minimally altered, consistent with the finding that serum ethanol concentrations in the dam were less than 10% of the levels found in the pup, which is likely due to increased ability to metabolize ethanol in the dams.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have also demonstrated FAE-induced decreases in allopregnanolone potentiation of [ 3 H]flunitrazepam binding to hippocampal GABA A Rs in guinea pigs [100], age-dependent changes in a5 GABA A R subunit expression in mice [101], and increased d GABA A R subunit expression and sensitivity to THIP in cerebellar granule neurons of rats after early postnatal (P2-12) EtOH vapor exposure [102]. Neurosteroids, such as 3a,5a-3-hydroxypregnan-20-one (3a,5a-THP or allopregnanolone) and 3a;5a-tetrahydrodeoxycorticosterone (THDOC), are potent endogenous modulators of d subunitcontaining GABA A Rs [103].…”
mentioning
confidence: 97%
“…Although the Catwalk test only revealed subtle deficits in locomotion and gait, it is possible that the rats were able to compensate for the damage caused by the third trimester-ethanol exposure-induced micro-hemorrhages or that this test lacks sufficient sensitivity to detect motor alterations secondary to the brain micro-hemorrhages. We previously found that ethanol vapor exposure for 4 hr/day during P2-P12 (peak pup blood ethanol levels near 0.3 g/dl) delayed the acquisition of the air-righting reflex, which was evident at P14-P18 (Diaz et al, 2014). Consequently, a more detailed assessment of sensorimotor and cognitive functions in these animals is clearly warranted, including an in-depth characterization of these across different developmental time points.…”
Section: Discussionmentioning
confidence: 98%